Towards a Fair Agro-food Regime? A Regulationist Reading of the Fairtrade System - Juan Ignacio Staricco (Revue de la Régulation)
The hypothesis of an emerging corporate-environmental food regime postulates that accumulation in the sector is based on the organization of quality audited supply chains governed by corporations. However, this reorganization of the food regime is being done on the basis of the appropriation of demands for a more socially, economically and environmentally sustainable agri-food system. This article proposes to examine the certification-based Fairtrade initiative as an entry point to the discussion of the potentiality of a corporate-environmental food regime. To do so, a regulationist conceptual framework is put forward in order to analyze the case of Fairtrade wine produced in Argentina and consumed in the United Kingdom. The analysis is done in two parts: first, by describing the concrete ways in which the Fairtrade mode of regulation institutionalizes socioeconomic relations; second, by reconstructing the Fairtrade concept of control in order to account for the political dynamics and ideological elements that underlie this system. The analysis concludes that the Fairtrade mode of regulation offers a very limited scope for transformation due to the inherent limitations imposed by the central role that capital fractions are given in the system.